ANALISIS PENGARUH STOCK SPLIT TERHADAP HARGA SAHAM PADA PERUSAHAAN GO PUBLIC DI BURSA EFEK INDONESIA - Suryansyah, Ahmad; Zandra, Rosy Aprieza Puspita; Tamami, Hairut (JURNAL AKUNTANSI DAN INVESTASI, 2018)
The stock split action will create a mirage effect for investors, namely investors will feel as if they are more prosperous because they hold more shares. So, stock split is an action that has no economic value. However, many of the stock split events in the capital market indicate that stock split is an important tool in capital market practices. The population in this study is a stock split company which is listed on the Indonesia Stock Exchange (IDX), which number 28 companies. And the sample in this study is 26 companies. The sample collection technique uses purposive sampling technique that is the sample taken based on certain criteria. The analytical tool used in this study is the Paired Sample Test. Based on the results of the study using different tests, there is no significant difference between the relative stock prices before the announcement of the stock split and after the announcement of the stock split.